Growth and survival of marine sponges, Stylissa massa (Carter, 1887) and Liosina paradoxa (Thiele, 1899) in sea and land based culture systems - Kiruba Sankar, R.; Chadha, N. K.; Dam Roy, S.; Banerjee, Paramita; Saharan, Neelam; Krishnan, P. (Indian Journal of Fisheries, 2016)
Two species of marine sponges Stylissa massa and Liosina paradoxa were cultured in cages (in situ) and in land based aquaria (ex situ) over a period of 120 days. Growth and survival were evaluated using four substrates viz., tile, block, coral rock and rope) under both in situ and ex situ conditions. L. paradoxa in cages recorded significant increase (p